Policy pathways through FinTech and green finance for low-carbon energy transition in BRICS nations - Bo Dai; Jian Zhang; Nasir Hussain (Energy Strategy Reviews)
This research examines the challenges faced by the BRICS countries, with a specific focus on issues surrounding energy production and environmental degradation. It investigates the potential of green financing and knowledge-for-money exchange to accelerate the transition to sustainable energy sources. This study employs sophisticated statistical methodologies to analyze the impact of economic variables, technological advancements, and ecological banking practices on the adoption of sustainable electricity utilization. The findings reveal a stable and positive relationship between the increase in the share of renewable energy sources, advancement in financial and technological sectors, the preservation of biological diversity, and the rational use of resources. The use of environmentally friendly energy solutions is particular sensitive to improvement in financial technology (FinTech) and sustainable funding sources. However, reliance on exploiting natural resources poses challenges to fully adopting low-carbon energy policies. This research underscores the critical importantance of environmental conservation and adocates for the use of sustainable funding mechanisms and financial innovation to implement effective policies for transitioning to low-carbon energy systems.